Leveraging Image Processing for Cloak Invisibility (International Journal of Innovative Research in Engineering & Management, 2023)
Substance classified as retro-reflective is  used to make the cloak, which is used for visual conceal ment purposes. Particles of retro-reflective substance  occupy a broad surface area. It's impossible to tell where  the flashes of illumination come from as they hit these  beads. Utilizing the color information of a certain colour,  we must obscure the picture's backdrop in this applica tion. I'm utilizing red, black, blue, and white to create the  above notion. The programme will translate the shade to  HSV style and pick the correct top and bottom limit val ues to identify the hue variations and then conceal it if the  colour is present in the picture.
Keywords: Image Processing; Hue; Color Information; Cloak Invisibility